Impact of age on outcomes of patients assisted by veno-arterial or veno-venous extra-corporeal membrane oxygenation: 403 patients between 2005 and 2015. (May 2020) - Marie, Basile; Anselmi, Amedeo; Flecher, Erwan; Nesseler, Nicolas; Launey, Yoann; Tadie, Jean-Marc; Verhoye, Jean-Philippe
Introduction: To assess the impact of age on early outcomes and mortality in veno-arterial extra-corporeal membrane oxygenation and veno-venous extra-corporeal membrane oxygenation recipients, and to investigate predictors of mortality. Methods: Single-center retrospective study on prospectively collected data including all patients treated by veno-venous extra-corporeal membrane oxygenation and veno-arterial extra-corporeal membrane oxygenation (January 2005-July 2015). Outcomes were compared among two subgroups: aged less than 65 years (Group 1) versus more than 65 years (Group 2) and by type of support (veno-arterial extra-corporeal membrane oxygenation or veno-venous extra-corporeal membrane oxygenation). Results: Among 403 patients, 20.3% were treated by veno-venous extra-corporeal membrane oxygenation and 79.7% by veno-arterial extra-corporeal membrane oxygenation. Veno-arterial extra-corporeal membrane oxygenation group: 76.6% were included in Group 1 and were more severe (pH 7.30 ± 0.19 vs. 7.35 ± 0.13 in Group 2, p = 0.003; lactates 7.5 ± 5.6 mmol/L vs. 5.8 ± 4.5 mmol/L in Group 2, p = 0.003). Weaning rate was higher in Group 1 (63.8% vs. 45.3%, p = 0.0043). The 30-day survival was higher in Group 1 (52.0% vs. 25.3%, p < 0.001). Univariate analysis identified higher Simplified Acute Physiology Score II (p = 0.02) and noradrenaline (p = 0.04) to be associated with mortality. Veno-venous extra-corporeal membrane oxygenation group: 80.5% were in Group 1. Mean PaO2 was 73.5 ± 42.9 mm Hg versus 100.8 ± 80.3 mm Hg (p = 0.24); FiO2 90.1% ± 18% versus 89.4% ± 16.4% (p = 0.89); and 30-day survival 56.1% versus 25.0% (p = 0.048). Conclusion: Patients older than 65 years have higher mortality after veno-arterial extra-corporeal membrane oxygenation or veno-venous extra-corporeal membrane oxygenation. This therapeutic strategy is feasible in the elderly, but comorbidities and clinical presentation have a major impact on prognosis and need to be seriously considered to avoid futile treatment.